2018
DOI: 10.4103/ijccm.ijccm_197_18
|View full text |Cite
|
Sign up to set email alerts
|

A multicentric, prospective, observational antibacterial utilization study in Indian tertiary referral centers

Abstract: Rationale:Antibacterials are largely prescribed to the intensive care unit (ICU) patients due to high prevalence of infections. However, appropriate use of antibacterials is imperative; since the misuse of antibacterials increases antibacterial resistance and ultimately, it has negative impact on health care and economic system. Hence, continuous antibacterials prescription assessments are very important to judge and improve prescription patterns. The present work was carried out at public and private hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
5
2
0
Order By: Relevance
“…In our study, an average of 8 with a maximum of 18 drugs were prescribed per patient which was comparable or lower to earlier studies conducted in similar settings from India as well as abroad [ 7 , 11 , 15 , 16 ]. Polypharmacy (five or more drugs prescribed) was observed (99%) which was in line with some earlier studies from India [ 17 - 20 ]. Panamanian et al, however, reported only 57% incidence of polypharmacy [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, an average of 8 with a maximum of 18 drugs were prescribed per patient which was comparable or lower to earlier studies conducted in similar settings from India as well as abroad [ 7 , 11 , 15 , 16 ]. Polypharmacy (five or more drugs prescribed) was observed (99%) which was in line with some earlier studies from India [ 17 - 20 ]. Panamanian et al, however, reported only 57% incidence of polypharmacy [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…An overuse of pantoprazole (97% of patients) was observed, a finding in agreement with earlier studies [11,[13][14][15][16][17][18][19][20][21]. Proton pump inhibitors reduce stomach acid output, inhibit upper gastrointestinal hemorrhage, and enhance mucosal healing.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Despite being an old antibiotic, vancomycin pharmacokinetics (PK) data in critically ill patients are limited and there are no data in Indian population. During our recent observational study, 12 we observed that vancomycin use is 23.23% in medical ICU without support of therapeutic drug monitoring services and evidence of pk data on vancomycin. Hence, present prospective single dose and steady state PK study was conducted in patients with suspected or proven gram-positive bacterial infections admitted to medical ICU.…”
Section: Introductionmentioning
confidence: 83%